Gatifloxacin versus ofloxacin for the treatment of uncomplicated enteric fever in Nepal: an open-label, randomized, controlled trial. - Samir Koirala; Buddha Basnyat; Amit Arjyal; Olita Shilpakar; Kabina Shrestha; Rishav Shrestha; Upendra Man Shrestha; Krishna Agrawal; Kanika Deshpande Koirala; Sudeep Dhoj Thapa; Abhilasha Karkey; Sabina Dongol; et al. (PLoS Neglected Tropical Diseases)
Background Fluoroquinolones are the most commonly used group of antimicrobials for the treatment of enteric fever, but no direct comparison between two fluoroquinolones has been performed in a large randomised trial. An open-label randomized trial was conducted to investigate whether gatifloxacin is more effective than ofloxacin in the treatment of uncomplicated enteric fever caused by nalidixic acid-resistant Salmonella enterica serovars Typhi and Paratyphi A. Methodology and principal findings Adults and children clinically diagnosed with uncomplicated enteric fever were enrolled in the study to receive gatifloxacin (10 mg/kg/day) in a single dose or ofloxacin (20 mg/kg/day) in two divided doses for 7 days. Patients were followed for six months. The primary outcome was treatment failure in patients infected with nalidixic acid resistant isolates. 627 patients with a median age of 17 (IQR 9-23) years were randomised. Of the 218 patients with culture confirmed enteric fever, 170 patients were infected with nalidixic acid-resistant isolates. In the ofloxacin group, 6 out of 83 patients had treatment failure compared to 5 out of 87 in the gatifloxacin group (hazard ratio [HR] of time to failure 0.81, 95% CI 0.25 to 2.65, p = 0.73). The median time to fever clearance was 4.70 days (IQR 2.98-5.90) in the ofloxacin group versus 3.31 days (IQR 2.29-4.75) in the gatifloxacin group (HR = 1.59, 95% CI 1.16 to 2.18, p = 0.004). The results in all blood culture-confirmed patients and all randomized patients were comparable. Conclusion Gatifloxacin was not superior to ofloxacin in preventing failure, but use of gatifloxacin did result in more prompt fever clearance time compared to ofloxacin. Trial registration ISRCTN 63006567 (www.controlled-trials.com).